An investigation on phenological and pomological traits of some almond cultivars grown at Ceylanpinar State farm in Turkey - Ak B.E.; Kuzdere H.; Kaska N. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This experiment was carried out at Beyazkule in Ceylanpinar State Farm in Sanliurfa. The phenological and pomological characteristics of 21 almond types or cultivars (8 Turkish, 2 French, 3 American, 4 Russian, 2 Spanish and 2 Italian) planted at CEYTAM are presented. According to the obtained data, nut sizes were small in almost all cultivars. Yields were satisfactory in some cultivars while low in the others. As a result of these, it was assumed that, at least, 'Garrigues', 'Cristomorto' and 'Ferraduel' can be recommended for this region.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)